The Effect of Enteral Nutrition with Low-Dose Lactulose on the Occurrence of Late-Onset Neonatal Sepsis in Infants with Very Low Birth Weight - Amir Mohammad Armanian; Shamim Shafieiyoon; Shaghayegh Dehghani; Elaheh Shirani; Nima Salehimehr (مجله دانشکده پزشکی اصفهان, 2019)
Background: This study aimed to investigate the effect of low-dose lactulose as a prebiotic on the prevention of sepsis in infants with very low birth weight.